Teenage grief - Bradshaw, Jane; Leeds Animation Workshop; Leaf Learning (Firm). ([United Kingdom] : Leaf Learning : Leeds Animation Workshop, 2007)
This animated video (six separate episodes) looks at young people, from different backgrounds, facing different kinds of bereavement.
Title from title screen.
Editor : Neil Stewart.
Narrated by Lenny Henry.
Keywords: Grief in adolescence; Bereavement in adolescence